TGF-beta-Mediated Suppression by CD4+CD25+ T Cells Is Facilitated by CTLA-4 Signaling - Oida, Takatoku; Xu, LiLi; Weiner, Howard L; Kitani, Atsushi; Strober, Warren (The Journal of immunology (1950), 2006)
CD4+CD25+ T cells play a pivotal role in immunological homeostasis by their capacity to exert immunosuppressive activity. However, the mechanism by which these cells function is still a subject for debate. We previously reported that surface (membrane) TGF-β produced by CD4+CD25+ T cells was an effector molecule mediating suppressor function. We now support this finding by imaging surface TGF-β on Foxp3+CD4+CD25+ T cells in confocal fluorescence microscopy. Then, using a TGF-β-sensitive mink lung epithelial cell (luciferase) reporter system, we show that surface TGF-β can be activated to signal upon cell-cell contact. Moreover, if such TGF-β signaling is blocked in an in vitro assay of CD4+CD25+ T cell suppression by a specific inhibitor of TGF-βRI, suppressor function is also blocked. Finally, we address the role of CTLA-4 in CD4+CD25+ T cell suppression, showing first that whereas anti-CTLA-4 does not block in vitro suppressor function, it does complement the blocking activity of anti-TGF-β. We then show with confocal fluorescence microscopy that incubation of CD4+CD25+ T cells with anti-CTLA-4- and rB7-1/Fc-coated beads results in accumulation of TGF-β at the cell-bead contact site. This suggests that CTLA-4 signaling facilitates TGF-β-mediated suppression by intensifying the TGF-β signal at the point of suppressor cell-target cell interaction.